2016
DOI: 10.1227/neu.0000000000001249
|View full text |Cite
|
Sign up to set email alerts
|

Failure of Mean Arterial Pressure Goals to Improve Outcomes Following Penetrating Spinal Cord Injury

Abstract: ASIA, American Spinal Injury AssociationMAP, mean arterial pressureSCI, spinal cord injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 28 publications
0
27
0
Order By: Relevance
“…66 Aggressive cardiopulmonary management following multisystem trauma involving the spinal cord should weigh equipoise between expected risk of complications and relatively lower likelihoods of recovery.…”
Section: Spinal Cord Perfusion and Vasopressor Supportmentioning
confidence: 99%
“…66 Aggressive cardiopulmonary management following multisystem trauma involving the spinal cord should weigh equipoise between expected risk of complications and relatively lower likelihoods of recovery.…”
Section: Spinal Cord Perfusion and Vasopressor Supportmentioning
confidence: 99%
“…4 In comparison to blunt SCI, a study by Readdy et al showed that vasopressor use did not improve neurological outcomes. 20 We also did not find any significant improvement in neurological outcome in patients who sustained penetrating injuries and were treated with vasopressors. The existing literature provides some guidance on surgical indication, reserving surgical intervention for progressive neurological deficit, spinal instability, or infection control.…”
Section: Discussionmentioning
confidence: 51%
“…Consequently, there is significant variability in penetrating spinal trauma management practices with most trauma centers relying on blunt spine trauma guidelines, which may be ill-equipped for the distinct patient population and mechanism of penetrating injury. 11,13,20 Our institution is an academic level 1 trauma center and safety-net hospital in the southeastern United States with a relatively high rate of penetrating spine injuries. 27 The goal of this study was to examine the epidemiology of penetrating spine injuries compared with blunt injuries.…”
mentioning
confidence: 99%
“…Additionally, maintenance for 5-7 days may be insufficient because certain individuals benefit from longer management [4]. One study has shown that vasopressor therapy achieving the MAP goal is more likely to cause complications than to improve neurological outcomes, with dopamine leading in complications [20]. As such, the risk of vasopressors should be balanced against their benefits in each individual patient, and there should be clear goals for use in regard to improvement of the sensory and motor deficits vs. cardiovascular stabilization.…”
Section: Patient Managementmentioning
confidence: 99%